Pengaruh Literasi Keuangan dan Penghasilan Pada Pengelolaan Keuangan dengan Kontrol Diri Sebagai Variabel Intervening di TVRI Pusat - Fauzia, Dwi Vina; Abdullah, Thamrin; Karunia, Luki (Jurnal Sosial Teknologi, 2025)
This study aims to analyze the influence of financial knowledge and income on financial management behavior with self-control as an intervening variable among employees of the Public Broadcasting Institution of Television of the Republic of Indonesia (LPP TVRI) Head Office. This research employs a quantitative approach using the Partial Least Square (PLS) method to test the measurement and structural models. The research sample consists of 268 employees selected through purposive sampling techniques. The results indicate that financial knowledge and income have a significant positive effect on financial management behavior. Furthermore, self-control acts as a mediating variable that strengthens the relationship between financial knowledge, income, and financial management behavior. These findings emphasize the importance of improving financial literacy and enhancing self-control to promote prudent financial management behavior among employees. The practical implications of this study suggest that the LPP TVRI Head Office should implement financial literacy training programs and incentive strategies that support employees' self-control in managing their finances. This study contributes theoretically to the development of financial management studies regarding self-control as a mediating variable.